ENVIRONMENTAL ANALYSIS STUDY CHALLENGE CHALLENGES FOR VIETNAM CASHEW EXPORT MARKET – A STUDY AT PLEIKU - Tram, Đỗ Thị Thanh (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2022)
Plantation is one of the minor industries in agriculture with a strategic role and contribution to the Vietnamese economy. One of those items is cashew nuts. This research aims to analyze cashew competitiveness in the international market to identify factors affecting cashew's competitiveness and develop a strategy to improve cashew competitiveness. The research method used is SWOT. The results show that the value shows that Vietnam's cashew nuts have advantages and disadvantages, but Vietnam is still the largest exporter in the world because it is always in the top 3 comparing data with the world when see the value and market share of Vietnam cashew nuts based on the quantity of output and the monetary value converted due to different market prices each year